2021
DOI: 10.1016/j.sdentj.2020.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Use of chlorhexidine chip after scaling and root planning on periodontal disease: A systematic review and meta-analysis

Abstract: Objective This systematic review aims to assess the efficacy chlorhexidine chip as an adjunctive therapy of scaling and root planning on periodontal disease treatment. Material and methods This study follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines (PRISMA) and was registered in the PROSPERO database (CRD42019148221). The search was performed in PubMed/MEDLINE, Scopus, and Cochrane databases until April 2020. The PICO question was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The use of different biomaterials in periodontal regeneration has been studied for years. Several treatment options for periodontal disease include open flap debridement (OFD), biologically active regenerative materials, bone-replacement graft materials, scaling and root planning, and guided tissue regeneration with barrier membranes [87][88][89][90][91][92]. The combined use of barrier membranes and biomaterials was shown to be more effective than using OFD alone.…”
Section: Dental Therapymentioning
confidence: 99%
“…The use of different biomaterials in periodontal regeneration has been studied for years. Several treatment options for periodontal disease include open flap debridement (OFD), biologically active regenerative materials, bone-replacement graft materials, scaling and root planning, and guided tissue regeneration with barrier membranes [87][88][89][90][91][92]. The combined use of barrier membranes and biomaterials was shown to be more effective than using OFD alone.…”
Section: Dental Therapymentioning
confidence: 99%
“…It has been shown that the number of pockets ≥7 mm-deep that reduced ≥2 mm was almost doubled in patients treated with SRP plus CHX Gluconate Chip compared to SRP alone [ 52 ]. Improvement of pocket depth (PD), Clinical Attachment Level (CAL) with the CHX Gluconate Chip as an adjunct to SRP has also been shown for pockets ≥ 5 mm [ 17 ]. Moreover, studies have shown mean improvement in PD between 2.3 and 3.4 mm and CAL gain 1.0–2.3 mm [ 53 ].…”
Section: Non-surgical Management Of Periodontitismentioning
confidence: 99%
“…Specifically for periodontitis and peri-implantitis, commonly used anti-biofilm agents include a variety of antibiotics and the antiseptic chlorhexidine (CHX), which can be delivered systemically or locally [ 13 , 14 , 15 , 16 , 17 ]. Different systematic reviews have compared traditional non-surgical mechanical treatment for periodontitis and peri-implantitis with debridement combined with anti-biofilm agents or anti-biofilm agents alone [ 13 , 15 , 16 , 17 , 18 ]. For local delivery antibiotics, the results are still controversial [ 13 , 15 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the effective treatment of periodontitis is vital for a healthy life. Conventional treatment approaches to periodontitis including non-surgical, surgical, and adjunctive pharmacological therapy have limitations, such as residual bacterial and calculus in the deep periodontal pocket, limited effect on inflammation regulation, limited periodontal tissue regeneration, and lack of consideration of the effect of systemic diseases (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%